Project Portfolio Management Model for an Arts E-Commerce Microenterprise - Sassi, Bruno de Arantes Leite (2023)
The objective of this work was to propose guidance parameters to the managers of a small company for the improvement of decision-making related to the management of project portfolio. This, through the establishment of a methodology with homogeneous and clear criteria, based on the consolidation of the data of the different initiatives present in the portfolio of the organization studied. The exploratory research was carried out through a qualitative and quantitative case study of an e-commerce microenterprise in the arts segment. The current scenario of the company was characterized and a management model was proposed with processes for maximizing performance, monitoring and control of the project portfolio. Also, thus verifying points of attention in relation to the financial risks of the consolidated portfolio, as well as opportunities to balance product lines and types and to identify the importance of balancing financially attractive initiatives with strategic projects for long-term goals. The main contribution of the work, however, was the formalization of the project portfolio management process, which will allow the company to optimize the allocation of its resources in pursuit of its organizational objectives.